MicroRNA Deregulation in Anaplastic Thyroid Cancer Biology - Cesar Seigi Fuziwara; Edna Teruko Kimura (International Journal of Endocrinology)
Anaplastic thyroid cancer (ATC) is among the most lethal types of cancers, characterized as a fast-growing and highly invasive thyroid tumor that is unresponsive to surgery and radioiodine, blunting therapeutic efficacy. Classically, genetic alterations in tumor suppressor TP53 are frequent, and cumulative alterations in different signaling pathways, such as MAPK and PI3K, are detected in ATC. Recently, deregulation in microRNAs (miRNAs), a class of small endogenous RNAs that regulate protein expression, has been implicated in tumorigenesis and cancer progression. Deregulation of miRNA expression is detected in thyroid cancer. Upregulation of miRNAs, such as miR-146b, miR-221, and miR-222, is observed in ATC and also in differentiated thyroid cancer (papillary and follicular), indicating that these miRNAs’ overexpression is essential in maintaining tumorigenesis. However, specific miRNAs are downregulated in ATC, such as those of the miR-200 and miR-30 families, which are important negative regulators of cell migration, invasion, and epithelial-to-mesenchymal transition (EMT), processes that are overactivated in ATC. Therefore, molecular interference to restore the expression of tumor suppressor miRNAs, or to blunt overexpressed oncogenic miRNAs, is a promising therapeutic approach to ameliorate the treatment of ATC. In this review, we will explore the importance of miRNA deregulation for ATC cell biology.